2022
DOI: 10.1007/s00192-022-05137-1
|View full text |Cite
|
Sign up to set email alerts
|

A mobile app for the treatment of female mixed and urgency incontinence: a cost-effectiveness analysis in Sweden

Abstract: Introduction and hypothesis A previous randomized controlled trial (RCT) demonstrated that the app Tät II, for self-management of mixed urinary incontinence (MUI) and urgency urinary incontinence (UUI), yielded significant, clinically relevant improvements in symptom severity and quality of life (QoL) compared with a control group. We aimed to assess the cost-effectiveness of Tät II. Methods A cost–utility analysis with a 1-year societal perspective was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…10 Several studies have shown that reminders from the smartphone application are an effective strategy to increase the follow-up rate in terms of using PFMT to treat UI. 13,[15][16][17][18][19][20]31 Our study first assessed the adherence to regular smartphone application reminder-based PFMT and changes in pelvic floor function in women in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Several studies have shown that reminders from the smartphone application are an effective strategy to increase the follow-up rate in terms of using PFMT to treat UI. 13,[15][16][17][18][19][20]31 Our study first assessed the adherence to regular smartphone application reminder-based PFMT and changes in pelvic floor function in women in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based platforms and smartphone applications represent an increasingly common way of supporting self-management of PFMT for stress UI (SUI), which can significantly improve the adherence rate of PFMT and SUI symptoms. 13,[15][16][17][18][19][20] However, there were only a few studies that used apps to guide postpartum pelvic floor rehabilitation. This prospective randomized controlled study examined whether the smartphone application-based periodic reminder can improve the adherence and effect of postpartum PFMT.…”
Section: Why This Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the 18 studies in this review were conducted between 2016 and 2022. Of the 18 studies, 10 (56%) [30][31][32][33][34][35][36][37][38][39] were conducted in the United States; 2 (11%) [40,41] in the Netherlands; 2 (11%) [42,43] in Sweden; 1 (6%) [44] in Germany; 1 (6%) [45] in Japan; 1 (6%) [46] in the United Kingdom; and 1 (6%) [47] jointly in the Netherlands, Spain, and Taiwan. Furthermore, of the 18 studies, 10 (56%) [30][31][32][34][35][36][37][38][39]45] were industry funded, 6 (33%) [40,41,43,44,46,47] were publicly funded, and the remaining 2 (11%) [33,42] received mixed funding.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Regarding the type of EE performed, of the 18 studies, 7 (39%) [30][31][32][33][34][35][36] involved nonrandomized study-based EE, 6 (33%) [37][38][39]44,45,47] involved model-based EE, and 5 (28%) [40][41][42][43]46] involved RCT-based EE. Of the 18 studies, 12 (67%) used a payer perspective [30][31][32][33][34][35][36]38,39,41,45,46], whereas 6 (33%) used a societal perspective [37,40,[42][43][44]47], with 2 (11%) of the latter group also taking a payer perspective [37,47]. The time horizon used for the EE was between 6 and 12 months for 56% (10/18) of the studies [32][33][34][35][36][40][41][42][43]46]…”
Section: Study Characteristicsmentioning
confidence: 99%